Giant Hydronephrotic Kidney Masquerading as Urinoma: A Rare Presentation with Review of Literature - Sokhal, Ashok Kumar (Urol Case Rep, 2017)
Giant hydronephrosis (GH) is a condition in which pelvicalyceal system contains more than 1000 ml of urine. Common causes of GH are uretero-pelvic junction obstruction, renal calculus, abdominal trauma. We are reporting a case of 45 years’ male, who presented with abdominal trauma and haematuria and was suspected a urinoma secondary to renal trauma. Examination revealed soft, cystic abdominal lump. Computed tomography of the abdomen revealed grossly hydronephrotic right kidney. The patient was managed by pyeloplasty after renal scan (estimated plasma renal flow- 91.92 ml/minute). Giant hydronephrotic kidney presenting with history of trauma may be confused with post traumatic urinoma.